(Not) Thinking About the Future: Financial Information and Maternal Labor Supply - Ana Costa-Ramón; Michaela Slotwinski; Ursina Schaede; Anne Ardila Brenøe (The Quarterly Journal of Economics, 2026)
Abstract Does information about the long-run financial costs of reduced labor supply increase mothers’ working hours? We document descriptively that long-term financial factors are not top of mind when mothers decide on their employment level. Moreover, a substantial share of women holds overly optimistic expectations about pension receipt and wage growth under part-time work. In a large-scale field experiment in Switzerland, we randomly assign mothers working part-time as teachers to receive objective information about the long-run costs of reduced labor supply. The treatment increases both demand for financial information and future labor supply plans, in particular among women who underestimate the costs of part-time work. Leveraging linked employer administrative data one year post-intervention, we find that this group of mothers increases working hours by 7%. These findings underscore that policies reducing information frictions in labor supply decisions may help address remaining gender gaps in the labor market.